ANODISASI PADUAN AL 2024 T3 DENGAN METODE PULSE CURRENT DALAM LARUTAN ASAM TARTARAT-SULFAT (TSA) [A Preliminary Study of Corrosion for Ni3(Si,Ti) Intermetallic Compound With Various Temperatures in Neutral Sodium Chloride Solution] - Mubarok, M. Zaki; Wahyudi, Soleh; Odang, Fitrian; Suharto, Sutarno (Jurnal Metalurgi, 2015)
The intermetallic compound of Ni3(Si,Ti) containing L12 single phase, have been applied as a candidate for high temperature material. This prelimenary study have been investigated using immersion test and polarization test in neutral 0.5 M NaCl solution at ambient temperature,of 40 °C and 60 °C, where the morfology of the corroded spesimens were observed by scanning electron microscope. The susceptibility of intergranular corrosion for this compound increases with increasing the temperature of solutions. The increase of temperature contributes for the diffulty of stable film formation with decreasing passive regions. The corrosion resistance of the compound decreased with increasing temperature test. It is implies that intergranular attack of the compound took place due to the presence of boron in grain boundaries.